Spiritual Criminals: How the Camden 28 Put the Vietnam War on Trial - Nickerson, Michelle M. (University of Chicago Press, 2024)
Intro -- Contents -- List of Figures -- Introduction -- Part I: The Catholic Left -- 1. A Movement within a Movement -- 2. Civil Disobedience -- 3. One Big Catholic Movement Family -- Part II: Exit 4 to Camden -- 4. Camden Calls the Catholic Left -- 5. Where's Bob? -- Part III: Putting the Vietnam War and the FBI on Trial -- 6. Research, Preparations, and Communion -- 7. A Prosecution Disarmed by Loving Kindness -- 8. No Guilt, No Apologies -- 9. Aftermath and Results -- Conclusion: Is There Anything Left of the Catholic Left? -- Acknowledgments -- List of Abbreviations -- Notes -- Index.